CuI/Pd0 Cooperative Dual Catalysis: Tunable Stereoselective Construction of Tetra‐Substituted Alkenes. Issue 7 (21st January 2014) - Vercruysse, Sébastien; Cornelissen, Loïc; Nahra, Fady; Collard, Laurent; Riant, Olivier
Abstract This paper describes a tunable and stereoselective dual catalytic system that uses copper and palladium reagents. This cooperative silylcupration and palladium‐catalyzed allylation readily affords trisubstituted alkenylsilanes. Fine‐tuning the reaction conditions allows selective access to one stereoisomer over the other. This new methodology tolerates different substituents on both coupling partners with high levels of stereoselectivity. The one‐pot reaction involving a CuI/Pd0 cooperative dual catalyst directly addresses the need to develop more time‐efficient and less‐wasteful synthetic pathways.